Issues of terrorism on the internet in the wave of democratization of post-reform Indonesia: A semiotic analysis - Saifullah, Aceng Ruhendi (Universitas Pendidikan Indonesia, 2016)
The discourse of terrorism is a global issue but tends to be interpreted as controversial. This study sought to dismantle the controversy of meanings through the analysis of signs and meanings, with a view to explore and demonstrate the wave of democratization that took place in post-reform era in Indonesia. This study was a case study using readers’ responses to terrorism issues provided by cyber media on the Internet. It also rests primarily on the semiotic theory of Peirce and the concept of democratization of Huntington. The results showed that participation, freedom of expression, and equal power relations occurred in the interactive discourse in the cyber news media in the form of a dialogue between the responders, the media, and the debate among the responders. Responders tended to argue that signs and meanings are constructed by the media and to interpret information about terrorism as